Behavioral and cognitive data in mice with different tryptophan-metabolizing enzymes knocked out - Too, Lay Khoon (Data Brief, 2016)
This article demonstrates behavioral changes in mice in response to free adaptation and drinking session adaptation modules implemented in their social home environment, the IntelliCage. These data complement the study “Deletion of TDO2, IDO-1 and IDO-2 differentially affects mouse behavior and cognitive function” (Too LK, Li KM, Suarna C, Maghzal GJ, Stocker R, McGregor IS, et al., 2016) [1]. Prior to programmed drinking sessions, all mice were exposed to a home cage adaptation module during which there was no time limit on water access – the free adaptation module. The exploratory behaviors are here expressed as percentages of visits with nosepokes and of visits with licks. The measurements by percentage of exploratory activity showed minimal genotype effects. The number of nosepokes or licks per corner visit also was compared between WT and gene knockout (GKO) IDO1 mice, WT and GKO IDO2 mice and WT and GKO TDO2 mice and demonstrated unremarkable behavioral changes during the free adaptation module. Analysis of drinking session adaptation behavior showed no genotype effect between WT and GKO of IDO1, IDO2 or TDO2 background. Notwithstanding the absence of genotype differences, each IDO1, IDO2 or TDO2 animal group displayed a specific pattern of adaptation to the drinking session modules. Furthermore, IDO1 GKO mice showed a more rapid recovery of lick frequency to the baseline level compared to the WT equivalents in a simple patrolling task during the first complete testing cycle (R1). TDO2 GKO mice on the other hand did not differ from their WT equivalents in terms of lick frequency over the three test days of complex patrolling and discrimination reversal tasks. Lastly, IDO2 GKO mice reduced their visits to the permanently non-rewarding reference corners by the same degree as did the WT mice.